RESEARCH TRENDS AND FUTURE DIRECTIONS ON SUSTAINABILITY REPORTING AND FIRM VALUE: A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Yohanes Fabiyola Halan; Ruth Trenyce Rade Tahulending (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
The value of Sustainability Reporting is steadily becoming more significant for advancing corporate transparency, accountability, and the fostering of enduring worth, signifying the elevated demands for conformity with environmental, social, and governance (ESG) expectations. The depth of the investigative work done varies, yet the comprehension of how Sustainability Reporting influences Firm Value is still scattered and shows significant discrepancies among different industries, nations, and organizational frameworks. This academic inquiry aims to rigorously analyze the extant literature, evaluate the enduring relevance of Sustainability Reporting in influencing Firm Value, elucidate the fundamental strategic frameworks that facilitate this relationship, and scrutinize its theoretical and practical implications for forthcoming research activities. This investigation employs a Systematic Literature Review augmented by Bibliometric analysis in accordance with the PRISMA guidelines. A comprehensive examination was conducted utilizing VOSviewer on 103 academic articles indexed in Scopus, published by May 9, 2026, to discern trends in publication frequency, keyword associations, collaborative interactions, and thematic evolutions. The findings indicate that Sustainability Reporting constitutes a crucial and rapidly expanding domain of inquiry, propelled by the proliferation of ESG regulations, stakeholder demands, and the strategic role of non-financial disclosures in mitigating information asymmetry and enhancing market valuation. This examination serves a critical function within the academic landscape by integrating diverse perspectives, identifying emerging challenges, and proposing pathways for future research that are of significance to scholars, practitioners, and policymakers alike.